2011
DOI: 10.1212/wnl.0b013e3182152830
|View full text |Cite
|
Sign up to set email alerts
|

Reduced uptake of [ 18 F]FDOPA PET in asymptomatic welders with occupational manganese exposure

Abstract: Background: Welding exposes workers to manganese (Mn) fumes, but it is unclear if this exposure

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 35 publications
3
85
0
Order By: Relevance
“…Similarly, neuropathological examinations in humans with symptomatic clinical Mn toxicity reveal degeneration of the medial segment of the globus pallidus with less severe degeneration of the putamen and caudate 13. Additional evidence that welding affects non-pallidal basal ganglia structures comes from the observation that PET measured uptake of [ 18 F]FDOPA is reduced in the caudate of asymptomatic welders 14. Together these findings suggest that extra-pallidal hyperintensities are likely present in occupationally exposed welders.…”
Section: Introductionmentioning
confidence: 96%
“…Similarly, neuropathological examinations in humans with symptomatic clinical Mn toxicity reveal degeneration of the medial segment of the globus pallidus with less severe degeneration of the putamen and caudate 13. Additional evidence that welding affects non-pallidal basal ganglia structures comes from the observation that PET measured uptake of [ 18 F]FDOPA is reduced in the caudate of asymptomatic welders 14. Together these findings suggest that extra-pallidal hyperintensities are likely present in occupationally exposed welders.…”
Section: Introductionmentioning
confidence: 96%
“…The largest molecular imaging study of the presynaptic dopaminergic system (the pathway primarily affected in PD) demonstrated dopaminergic dysfunction in Mn-exposed welders. 40,41 Although the pattern of dopaminergic dysfunction was different from that seen in PD, findings from molecular imaging of the dopaminergic system in patients with Mn toxicity secondary to liver failure suggest that the pattern of dopaminergic dysfunction may be more typical of PD. 42,43 Much of the epidemiological research conducted to date suffers from severe limitations.…”
Section: Discussionmentioning
confidence: 99%
“…This could explain the clinical phenotype associated with Mn neurotoxicity in which neuropsychiatric symptoms, including cognitive impairment, depression, and hallucinations, are often present before or concurrent with motor symptomatology, which would be unusual in early IPD. [125][126][127] The differences between early PET studies by Wolters et al 116 and subsequent studies may be related to differences in the method of Mn exposure, upgrades in scanner resolution, or more likely sample size, because these studies were not powered to detect the approximately 10% difference in [ 18 F]-fluoro-L-dopa uptake identified by Criswell et al 123 While these [ 18 F]-fluoro-L-dopa PET studies demonstrate evidence of presynaptic dopaminergic dysfunction, [ 18 F]-fluoro-L-dopa measurements alone cannot distinguish a neurotoxic effect on nigrostriatal neurons from a dysfunctional process causing a regulatory effect on presynaptic decarboxylase activity. In combination with the non-human primate studies by Guilarte et al,112 these findings support the hypothesis that chronic Mn exposure produces clinical neurotoxicity through presynaptic dopamine terminal dysfunction.…”
Section: Pet Studies In Human Subjectsmentioning
confidence: 99%